Adsorptive removal of methylene blue from aqueous solution using coal fly ash-derived mesoporous silica material - Ning Yuan; Hui Cai; Tian Liu; Qi Huang; Xinling Zhang (Adsorption Science & Technology)
In the present work, coal fly ash-derived mesoporous silica material (CFA-MS) has been successfully fabricated without employing any extra silica source. The obtained CFA-MS was characterized by Fourier transform infrared spectroscopy, nitrogen adsorption–desorption measurement, powder X-ray diffraction and transmission electron microscopy. Nitrogen adsorption–desorption measurement disclosed that CFA-MS possesses Brunauer–Emmett–Teller-specific surface area of 497 m 2 ·g −1 and pore volume of 0.49 cm 3 ·g −1 , respectively. Furthermore, CFA-MS was evaluated for the adsorptive removal of methylene blue from aqueous solution. Several influence parameters on the removal of methylene blue including contact time, pH, initial concentration and temperature were studied in detail. Moreover, Langmuir, Freundlich, Temkin and Dubinin-Radushkevich isotherm models were employed for interpretation of the adsorption process, while the pseudo-first-order and pseudo-second-order kinetics equations were applied to investigate the adsorption kinetics. Results in the current work demonstrate that CFA-MS can be used as an efficient adsorbent for methylene blue removal.